Hyperlink: A Generic Tool for Exploratory and Expressive Teaching and Learning in History. Issue 1 (1st December 2000) - Watson, Kate; O'connell, Kevin; Brough, Derek
Abstract : A major challenge of the micro-computer's impact upon history education has been to identify the unique qualities that it brings to teaching and learning. The issue is simple: what is the value-added factor that conventional pedagogy cannot provide? The initial response to using the micro-computer was to see it as a tool for processing data more quickly and effectively than conventional means. However, because data handling was only a small proportion of the educational process this failed to answer the bigger question of how it could transform education. Within this context Seymour Papert's revolutionary use of LOGO to provide a computer-mediated environment appeared to be the Holy Grail that we had been looking for. Central to LOGO and related developmental work was the creation of micro-worlds, mental models which were used both to express understanding of situations and to promote related problem solving through the exploration and transformation of the micro-world. The early developmental work on micro-worlds and their use in the classroom proved transitory: a major factor being the technical problems involved in creating the content-free software that allowed for the construction of micro-worlds. In 1999 we returned to the area when we realised that the technical problems could be largely resolved through use of Microsoft's hyperlink facility in Word. This enabled us to explore the potential of a range of exploratory micro-worlds for teaching and learning in the domain of history, both in the training of postgraduate students, training courses for practicing teachers and in the teaching of pupils. The paper reports upon the initial stages of this research and developmental work within the context of a PGCE history course, TTA funded History INSET.